Caregiving burden, depression, and anxiety among family caregivers of patients with cancer: An investigation of patient and caregiver factors - Karimi Moghaddam, Zhaleh; Rostami, Mina; Zeraatchi, Alireza; Mohammadi Bytamar, Jahangir; Saed, Omid; Zenozian, Saeedeh (Frontiers in Psychology, 2023)
Background Caring for patients with cancer can result in significant burden, anxiety, and depression among family caregivers, leading to alterations in their mental and physical wellbeing. Evidence on the level of cancer caregivers' burden, depression, anxiety, their role in assisting their patients, and other patient and caregiver factors that play in improving/worsening the outcomes, is limited. This study explored the prevalence of caregiving burden, depression, and anxiety with a focus on the patient and caregiver-related factors among cancer family caregivers. Methods A cross-sectional study was conducted on the population of caregivers of adult patients with cancer in Zanjan, Iran between 2019 and 2020. The Beck Depression Inventory (BDI), the Beck Anxiety Inventory (BAI), and the Zarit Burden Inventory (ZBI) were used to measure outcome variables. Clinical and basic characteristics of the caregivers and patients were also collected. An independent samples t-test, analysis of variance, Pearson's correlation coefficient, and stepwise linear regression were performed using SPSS software version 26. Results Mean ± standard deviation age of the caregivers (167 men and 133 women) was 40.77 ± 12.56. Of the caregivers, 46.3, 53, and 30.7% showed severe depression, anxiety, and burden, respectively. There was a significant positive correlation between ZBI with both BDI [r(298) = 0.19, p < 0.01] and BAI [r(298) = 0.20, p < 0.01]. Caregiving ≥24 months (B = 14.36, p < 0.001), outpatient care setting (B = −12.90, p < 0.001), being retired (B = −12.90, p < 0.001), depression (B = 0.28, p < 0.001), supplemental health insurance (B = −7.79, p < 0.001), being illiterate (B = 7.77, p < 0.01), surgery (B = 8.55, p < 0.01), ECOG1 (B = 4.88, p < 0.01), and patient's age (B = 0.11, p < 0.05) were found to be significant predictors of caregiving burden. Conclusion High levels of depression, anxiety, and burden were observed among the caregivers of patients with cancer. These findings underline the importance of paying close attention to the needs and psychological challenges of this population.